The Effect of Sport Education Model through Badminton on Moderate-to-Vigorous Physical Activity - Agi Ginanjar; Adang Suherman; Tite Juliantine; Yusuf Hidayat (Universitas Pendidikan Indonesia, 2019)
This study was aimed at examining physical activity differences in each phase of SEM through badminton. The method used in this study was experimental research method with factorial design. Participants of this study were 40 junior high school students chosen through simple random sampling technique. The study used Polar RC3 GPS as the research instrument. The data analysis techniques used in the study was One-Way ANOVA. The result of the study found differences in moderate-to-vigorous physical activity in each phase of SEM through badminton games. The finding also showed that the achievement of moderate-to-vigorous physical activity in the badminton game tends to decrease in the final stage.